Implementation of Website-Based UI UX Using the Design Thinking Method: Case Study at PT Jesinra Makmur Group - Firdani, Ella Fadila; Hanif, Isa Faqihuddin; Muhammad Febriansyah; Widsono, Maulana Yusuf (LPPM Telkom University Surabaya, 2024)
In the era of globalization, the imported goods shipping industry is growing rapidly. PT Jesinra Makmur Group, as a provider of imported goods delivery services, needs to ensure that the user experience (UI/UX) on its website platform is optimal. This research aims to redesign the UI/UX of the PT Jesinra Makmur Group website using a Design Thinking approach. The Design Thinking method consists of several stages, namely empathize, define, ideate, prototype, and testing. In this research, researchers will understand user needs, identify problems, generate creative ideas, create prototypes, and test proposed solutions. This research uses the System Usability Scale (SUS) to measure the success of UI/UX design, and a score of 87.75% was obtained, which indicates a high level of excellence. This shows that users feel comfortable and that it is easy to use the website. The results of this research are expected to provide a better solution for PT Jesinra Makmur Group to provide an optimal user experience through their website. By implementing the Design Thinking method, it is hoped that PT Jesinra Makmur Group can improve the UI/UX of their website and provide better service to customers.